Jurnal Tesis Kontruksi Pendidikan Moderasi Beragama melalui Living Sunnah (2025) : Penelitian - Ummu Shufairo’ (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the construction of religious moderation education through the practice of Living Sunnah in Pelemwatu Village, Menganti District, Gresik Regency. The activities studied were the habituation of praying tasbih and hajat in congregation every Friday Legi, which functioned not only as spiritual worship, but also as a means of educating the values ​​of tolerance, balance, and togetherness in society. The research method used a qualitative approach with an ethnographic study type. Data were obtained through participatory observation, in-depth interviews, and documentation. The results of the study showed that Living Sunnah is a form of non-formal education that is able to instill the values ​​of religious moderation contextually and effectively. These values ​​are conveyed through the exemplary behavior of religious figures, togetherness of residents, and internalization of socio-religious values ​​in everyday life.